Kaum Kedar: Tanggung Jawab Orang Percaya - Yeheskiel Obehetan (Jurnal Arrabona, 2023)
This study aimed to explore the mission of believers in sharing the gospel to the Kedar communities. Using library research method, the analysis find out: 1) The responsibilities of believers (loving and praying); 2) Reaching Kedar as the proof of the responsibility (mobilization, regeneration, and facilitate; and 3) Responsible parties (Theological seminary, church, missionary organization, communities, and all believers) A comprehensive understanding and responsibilities as believers could enable the disciples to have a new perspective about Kedar, also taking part in contextual evangelism, so Kedar communities could accept the Good News.